“. . .delivered from the lie of being truth”: The Affective Force of Disinformation, Stickiness and Dissensus in Randy Ribay’s Patron Saints of Nothing - Pacheco, Vincent; De Chavez, Jeremy (Text Matters: A Journal of Literature, Theory and Culture, 2021)
Waged in 2016, Philippine President Rodrigo Duterte’s war on drugs has claimed over 20,000 lives according to human rights groups. The Duterte administration’s own count is significantly lower: around 6,000. The huge discrepancy between the government’s official count and that of arguably more impartial organizations about something as concretely material as body count is symptomatic of how disinformation is central to the Duterte administration and how it can sustain the approval of the majority of the Philippine electorate. We suggest that Duterte’s populist politics generates what Boler and Davis (2018) call “affective feedback loops,” which create emotional and informational ecosystems that facilitate smooth algorithmic governance. We turn to Patron Saints of Nothing, a recently published novel by Randy Ribay about a Filipino-American who goes back to the Philippines to uncover the truth behind the death of his cousin. Jay’s journey into the “heart of darkness” as a “hyphenated” individual (Filipino-American) allows him access to locally networked subjectivities but not its affective entanglements. Throughout the novel, he encounters numerous versions of the circumstances of Jun’s demise and the truth remains elusive at the end of the novel. We argue that despite the constant distortion of fact and fiction in the novel, what remains relatively stable or “sticky” throughout the novel are the letters from Jun Reguero that Jay carries with him back to the Philippines. We suggest that these letters can potentially serve as a form of “dissensus” that challenges the constant redistribution of the sensible in the novel.